TPS progress report no. 4 entitled Engineering properties of the Sergipe clay. Volume I, Main text / by Charles C. Ladd, Shun-Min Lee. - Ladd, Charles C. (Charles Cushing); Lee, Shun-Min.; Odebrecht (Firm); Massachusetts Institute of Technology. Department of Civil and Environmental Engineering. (Tufts University. Tisch Library., 2019)
1 online resource : illustrations.; "Prepared for Constructora Noberto Odebrecht S.A."; "The work described in this report was performed under an Office of Sponsored Programs contract entitled "Geotechnical Studies for an Offshore Breakwater" between Constructora Noberto Odebrecht S.A. (CNO) and the Massachusetts Institute of Technology (MIT) that was initiated January 15, 1992"--Foreword.; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.